Effect of Differences of HCl Concentration on the Reaction of Chlorine Gas and Acetylene Gas In Clothing Liquids and Floor Cleaning Liquids - Salsabila Tambunan; Maya N Sari; Lia M Nasution; Siti Rahmah; Nurfajriani Nurfajriani (Universitas Negeri Medan, 2021)
Floor cleaning fluid containing a solution of HCl mixed with carbide (CaC2), produces a reaction in the form of gases, air bubbles and there is sedimentation. The resulting gas is acetylene gas. NaClO solution in clothes bleach reacts with HCl in floor cleaning fluid to produce a reaction in the form of an explosion of fire, soot / carbon and produces chlorine gas. This study aims to determine the effect of differences in the concentration of HCl in floor cleaning fluid to produce the reaction of chlorine gas and acetylene gas by mixing floor cleaner with carbide and clothes bleach. In this study, using a floor cleaner with a concentration of 12% HCl and a concentration of 17% as a comparison. The results obtained are that the difference in the concentration of HCl has an effect on explosions, gases.